Effects of social comparison on variety-seeking behavior: the roles of lack of perceived control and self-reflection - Che, Cheng; He, Yuxin; Zhou, Miaomiao (Frontiers in Psychology, 2025)
BackgroundSocial comparison, especially upward social comparison, has always been a common concern and experience in people’s lives. Although social comparison and its consequences have been extensively studied in previous literature, few scholars have paid attention to its influencing mechanism and boundary conditions on the compensatory consumption of variety-seeking.ObjectiveThis study used experimental methods to investigate whether social comparison is related to variety-seeking behavior, and to explore the mediating role of lack of perceived control and the moderating role of self-reflection.MethodsIn total, 414 participants were recruited for 3 experiments. They were divided into groups to complete their respective experimental tasks, including social comparison manipulation, variety-seeking manipulation, self-reflection manipulation, and lack of perceived control scale.ResultsThe results of the three experimental studies showed that compared with downward-comparison individuals, upward ones presented higher variety-seeking tendencies and the lack of perceived control mediated between the two, and that was moderated by self-reflection. Specifically, in the absence of self-reflection, upward comparisons will result in a higher propensity for variety-seeking behavior compared to downward ones. However, after engaging in self-reflection, the effect was no longer significant, while the mediating effect no longer held.ConclusionThe research highlights the relationship between social comparison and variety-seeking behavior, reveals the mediating mechanism between them, and deepens the understanding of how upward social comparison increases variety-seeking behavior. The above research results have positive significance for promoting the theory of social comparison, lack of perceived control and variety-seeking behavior, guiding the marketing practice of enterprises, and helping individuals reduce the negative impact of upward comparison.